The Study of Qualification Vulnerability of Islamic Councils in Iran’s System of Law - mohammad reza moein fard; mohammad kazem emad zadeh; morteza tabibi (تعاون و کشاورزی, 2018)
The history of local institutions in Iranian system of law is long in terms of having rules and regulations. However, achieving the desired goal has always faced various historical, political, cultural, economic and social barriers and obstacles. In the meantime, legal qualification (duties and authorities) barriers facing Islamic councils can be separately studied from the standpoint of different laws. The inherent contradiction of the principles of the Constitution in this regard, lack of having sufficient duties and authorities of councils and lack of separation of national and local affairs in ordinary law are among the most significant qualification obstacles facing urban and rural Islamic councils in Islamic Republic of Iran. In this respect, it seems necessary for the Guardian Council to provide a different interpretation of the Constitution befitting the status and dignity of Islamic councils and to employ the current capacities of councils as well as Legislature to have its efforts in enactment of appropriate laws.